Adaptive SMF Coupling Based on Precise-Delayed SPGD Algorithm and Its Application in Free Space Optical Communication - Guan Huang; Chao Geng; Feng Li; Yan Yang; Xinyang Li (IEEE Photonics Journal)
The adaptive coupling of laser beam from space into single-mode fiber (SMF) plays an important role in the fiber-based free space optical communication technology. This paper investigates a kind of adaptive SMF coupling system based on a novel corrector named adaptive fiber coupler, and an improved control algorithm named precise-delayed stochastic parallel gradient descent (PD-SPGD). Compared to the SPGD algorithm used previously, PD-SPGD can compensate for the inherent response delay of the controlled system by setting a precise time delay between the disturbed voltages and the performance metrics. The experimental results show that this new algorithm increases the iteration rate from 3 to 8 kHz and decreases the convergence time from 6.3 to 2.5 ms when the static angular errors was corrected. As a result, the control bandwidth of the sinusoidal angular jitters is more than doubled. At the end, a preliminary atmospheric compensation experiment over a 520 m near-ground propagation path is conducted to verify the effectiveness of the method mentioned above.